LEAFY TURNIP IS A NEW CROP FOR SALAD PRODUCTION LINES - V. A. Stepanov; S. M. Sirota; O. V. Antipova (Овощи России)
The collaborative work on growing of leafy turnip in condition of salad production line was conducted in ООО PKF «AGROTIP». The possibility of obtaining of ecologically safety salad turnip of cv. Selekta, Sapfir, and Biryuza at hydroponic system are shown. Data of yield, productivity, and content of ascorbic acid in green leaf of turnip growing in condition of flow hydroponic system are presented. The possibilities of using of tested turnip varieties in modern agrotechnological systems are discussed.